2009
DOI: 10.1002/anie.200903457
|View full text |Cite
|
Sign up to set email alerts
|

Stable Pentavalent Uranyl Species and Selective Assembly of a Polymetallic Mixed‐Valent Uranyl Complex by Cation–Cation Interactions

Abstract: Cation-cation interactions are a key feature of actinide chemistry. These interactions can be used in two areas that currently attract great interest, namely the expansion of felement supramolecular chemistry and the enhancement of magnetic interactions in actinide compounds. [1][2][3][4][5][6][7][8][9][10][11][12] Moreover, oligomeric cation-cation species that present mutually coordinated actinyl ions are likely to play a crucial role in nuclear waste reprocessing and in the migration of radioactive actinide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
71
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 44 publications
5
71
1
Order By: Relevance
“…[7,8] Usually the [UO 2 ] + cation decomposes by disproportionation, which is also a poorly understood process, but is important in the precipitation of uranium salts out of aqueous environments. [9,10] The disproportionation is suggested, by analogy with the transuranic metal oxo Lewis base behavior, to involve the formation of cation-cation interactions (CCIs) [11,12] in which the oxo groups ligate to adjacent actinyl centers forming diamond (A) or T-shaped (B) dimers or clusters which can then allow the transfer of protons and electrons between metals, such as in C. [13] We reported that the use of rigid, Pacman-shaped macrocycles can allow the isolation of heterobimetallic uranyltransition metal complexes that form an oxo interaction with the transition metal in the solid state and solution, [14] and how the inclusion of more than one metal cation alongside the uranyl cation led to isolable, stable pentavalent uranyl complexes with a covalently functionalized oxo group.…”
mentioning
confidence: 99%
“…[7,8] Usually the [UO 2 ] + cation decomposes by disproportionation, which is also a poorly understood process, but is important in the precipitation of uranium salts out of aqueous environments. [9,10] The disproportionation is suggested, by analogy with the transuranic metal oxo Lewis base behavior, to involve the formation of cation-cation interactions (CCIs) [11,12] in which the oxo groups ligate to adjacent actinyl centers forming diamond (A) or T-shaped (B) dimers or clusters which can then allow the transfer of protons and electrons between metals, such as in C. [13] We reported that the use of rigid, Pacman-shaped macrocycles can allow the isolation of heterobimetallic uranyltransition metal complexes that form an oxo interaction with the transition metal in the solid state and solution, [14] and how the inclusion of more than one metal cation alongside the uranyl cation led to isolable, stable pentavalent uranyl complexes with a covalently functionalized oxo group.…”
mentioning
confidence: 99%
“…Rigid carboxylate ligands were used widely in assembly with transition ions or lanthanides, because the rigidity of ligand is helpful to construct large rings or channels and the complicated coordination modes of carboxyl are good for structural diversity [2]. However, the complexes containing uranium (VI) centers have not been reported extensively [3], though they presented not only the diversity of their structures [4][5][6][7], but also potential applications in ion-exchange, magnetic property, and photo-catalysis [8][9][10]. The structures and properties of complexes formed by rigid carboxylate ligand and uranium ions are worthy of researching.…”
mentioning
confidence: 99%
“…[6] However, it has been shown recently that the more Lewis basic, pentavalent uranyl cation, [UO 2 ] + , can be stabilized indefinitely using suitable equatorial-binding ligands and anaerobic conditions. [7,8] Usually the [UO 2 ] + cation decomposes by disproportionation, which is also a poorly understood process, but is important in the precipitation of uranium salts out of aqueous environments. [9,10] The disproportionation is suggested, by analogy with the transuranic metal oxo Lewis base behavior, to involve the formation of cation-cation interactions (CCIs) [11,12] in which the oxo groups ligate to adjacent actinyl centers forming diamond (A) or T-shaped (B) dimers or clusters which can then allow the transfer of protons and electrons between metals, such as in C. [13] We reported that the use of rigid, Pacman-shaped macrocycles can allow the isolation of heterobimetallic uranyltransition metal complexes that form an oxo interaction with the transition metal in the solid state and solution, [14] and how the inclusion of more than one metal cation alongside the uranyl cation led to isolable, stable pentavalent uranyl complexes with a covalently functionalized oxo group.…”
mentioning
confidence: 99%